Characteristics of Idiopathic Sensory Processing Disorder in Young Children - Mulligan, Shelley; Douglas, Sarah; Armstrong, Caitlin (Frontiers in Integrative Neuroscience, 2021)
This study described the developmental and behavioral characteristics of children identified with idiopathic sensory processing disorder (SPD) as well as the relations among specific types of SPD as proposed by the nosology presented by Miller et al. (2007), adaptive behavior profiles, and behaviors associated with mental functioning. A retrospective, non-experimental design applying descriptive and correlational analyses was used. Data were obtained from clinic medical records of 78 children ages 2 to 7 years who were identified with sensory processing problems affecting daily life, but who did not meet criteria for any other neurodevelopmental or mental disorders following a comprehensive diagnostic evaluation. Results revealed that all SPD types as described by current typologies were well represented with the most common being the over-responsivity sensory modulation subtype. Within the sample, 53% of the children displayed more than one SPD type. Atypical externalizing and internalizing behavior scores associated with various mental disorders as measured by the child behavior checklist (CBCL) fell in the borderline dysfunctional range. Adaptive behavior for all developmental domains was below average, and the severity of SPD symptoms moderately and positively correlated with behaviors associated with mental disorders, and with lower adaptive behavior performance. It was concluded that symptoms characteristic of the various types of idiopathic SPD overlap substantially suggesting that current typologies may include more types/subtypes than are necessary or clinically useful. Children with SPD share similar, but often less severe pathological behaviors associated with other mental or related neurodevelopmental disorders. Psychometrically sound measures of SPD are needed, and further study of the neural mechanisms involved in sensory processing deficits is vital for validating idiopathic SPD as its own diagnostic entity.